Waste gas treatment in bioreactors: environmental engineering aspects. Issue 1 (1st January 2014) - Veiga, María C.; Montes, María; López, M. Estefanía; Kennes, Christian
Abstract : This paper gives an overview of the most important bioreactor configurations used in waste gas treatment, i.e., conventional and trickling biofilters, the bioscrubber, suspended-growth bioreactors, as well as two-liquid phase systems (stirred tank bioreactor and biotrickling filter). The historical evolution, main characteristics, and recent developments are described in each case.